2003
DOI: 10.1136/oem.60.12.910
|View full text |Cite
|
Sign up to set email alerts
|

Urine mutagenicity and lymphocyte DNA damage in fruit growers occupationally exposed to the fungicide captan

Abstract: Aims: To determine haematological parameters, urine mutagenicity (on three Salmonella typhimurium strains), and DNA damage (using the comet assay) in mononuclear leucocytes of farmers before and after a one-day spraying period of pear and apple trees with the fungicide captan in usual conditions. Methods: Fruit growers were exposed to captan during the 1998 (n = 12) and/or the 2000 spraying seasons (n = 17). Biological samples were collected on the morning of the day of spraying (S1), the evening after sprayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…After sorting, 2.10 5 cells were used to prepare 3 slides for comet assays, realized as previously described with minor modifications [52]. Electrophoresis was performed at 0.7 volts/cm for 26 min with the Sub-cell GT agarose gel electrophoresis system (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…After sorting, 2.10 5 cells were used to prepare 3 slides for comet assays, realized as previously described with minor modifications [52]. Electrophoresis was performed at 0.7 volts/cm for 26 min with the Sub-cell GT agarose gel electrophoresis system (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…25,26,28,29,31 Although most pesticides are thought to be nongenotoxic, 32 some pesticides have been shown to cause cytogenetic damage in laboratory assays, animal studies, or in humans. [33][34][35][36][37] Alternatively, pesticides may cause a second or later hit in lymphoid cells with the t(14;18), which ultimately leads to the occurrence of NHL. The t(14;18) joins the BCL2 gene on chromosome 18 to the immunoglobulin heavy chain gene on chromosome 14, resulting in an inhibition of programmed cell death through overexpression of the BCL2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…A small study evaluating the mutagenicity of post-exposure farmers' urine yielded inconclusive results [11]. An ecologic study suggested an increased risk of leukemia among Hispanic males and prostate cancer among black males in California counties where captan was used [12].…”
Section: Introductionmentioning
confidence: 97%